Exploring the Person-Centeredness of an Innovative E-Supportive System Aimed at Person-Centered Care: Prototype Evaluation of the Care Expert. Issue 5 (May 2016) - Ventura, Filipa; Koinberg, Ingalill; Sawatzky, Richard; Karlsson, Per; Öhlén, Joakim
Abstract : Integrated in a multiphase development project, the Care Expert is a prototype of a novel e-supportive system aiming to mediate person-centered care in the context of outpatient oncology. At this early stage of development, the current study was conducted aiming at exploring the person-centeredness concept underlying the Care Expert version 1.0 and its usability for patients receiving outpatient chemotherapy for breast cancer. Within a user-centered design, we followed a mixed-methods approach entailing subjective assessment and diagnostic evaluation of the prototype. Four women undergoing outpatient chemotherapy participated in individual sessions and rated highly the system's usability. Their accounts led to identifying three supportive functions: continuous communication, reinforcement of self-driven agency, and cooperative agency with a sense of being looked after. We discuss the results in relation to theoretical fields that might guide further the development of the supportive system and usability recommendations. Care Expert has the potential to mediate person-centered care in outpatient oncology. Nevertheless, additional cycles of iterative development with the software team and of participatory design focusing on oncology nurses' perspectives are required before departing to the feasibility phase in intervention research.